PENGARUH TATA KELOLA PERUSAHAAN DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2016-2022) - Nugraha, Ilham Ramadhan; Prastiwi, Arum (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to examine the effect of good corporate governance and intellectual capital on the company value of state-owned enterprises listed on the Indonesia Stock Exchange (IDX) between 2016 and 2022, involving secondary data obtained from the websites of IDX and respective companies. The samples in this study include 10 companies selected through the purposive sampling method and analyzed by multiple linear regression using the SPSS version 25 software. The dimension of good corporate governance is represented by the independent board of commissioners and the audit committee, and the intellectual capital dimension is represented by Value Added Intellectual Coefficient (VAIC). The results of the analysis exhibit that the audit committee and intellectual capital have a positive effect on company value, implying that a higher number of audit committees and intellectual capital value is capable of increasing company value. Whilst, the board of independent commissioners has a negative effect on company value, meaning that the higher proportion of independent commissioners is unable to improve company value.